Translatability of anaphora, cataphora, and ellipsis in order to keep the original meaning in the translation of the book el acarreo from Spanish into English - Osorio Cruz, Claudia Elizabeth
Literary devices are resources that are important in texts such as articles, stories, research papers, newspaper articles, etc. According to Quizlet’s definition (2017), a literary device is a set of literary resources that help to keep one single thematic in a text. These resources are applied by any writer. The use of these devices might vary from one language to another, but in the case of translators’ work, it is essential to keep the main idea of the source text. For that reason, these professionals have to know what literary figures stand for and their use. Besides, it is necessary to question some aspects of translating literary devices. How are these literary resources translated into the target language? Did these devices maintain or lose the main idea of the original text? To what extend the translation of these resources keeps the same meaning of the original text into the target language? All those questions emerge from the fact that every language has a different vision of the world and translators have to deal with a variety of situations that include the treatment of literary devices in the translation practice. The translation is a process whose goal is to produce a text in a target language with the same idea of the source text. The process to apply depends on the field. For instance, fields like Law might need to translate literally. Nonetheless, in the literary field, devices play an important role to comprehend the ideas. This is due to the message the author wants to transmit. During the translation process, the translator has to do a lot of research to avoid mistakes. The investigation includes the consult of other authors and translators; they also need to interview the authors; sometimes they need to check grammar, literary books, and other resources. Thus, the translation process leads to the production of an accurate text in 13 the target language, to succeed in this task, the translator’s role is crucial to preserve the literary resources, especially in texts that include literary devices that contain the main ideas or meanings.